In-beam range determination using an OpenPET system for helium, carbon, oxygen, and neon ion beams - Sun, Jiayao; Masuda, Takamitsu; Tashima, Hideaki; Toramatsu, Chie; Hamato, Akram; Yamaya, Taiga; Tanaka, Sodai; Kasamatsu, Koki; Mein, Stewart; Inaniwa, Taku (Physics in medicine and biology, 2025)
Objective. At the National Institutes for Quantum Science and Technology, helium, carbon, oxygen, and neon ion beams are utilized together in multi-ion therapy to enhance the therapeutic efficacy of charged-particle therapy. When accelerated ions traverse a medium, a fraction will undergo nuclear interactions, some of which, in turn, produce positron-emitting nuclei. This study investigates the accuracy of ion beam range determination using the annihilation photons emitted from the nuclei measured with an in-house online PET system (OpenPET). Approach. A polymethyl methacrylate phantom was irradiated separately with un-scanned helium, carbon, oxygen, and neon ion beams to 1.5 Gy physical doses at the Bragg peak. Annihilation photons were measured with OpenPET. Each irradiation was simulated using the Particle and Heavy Ion Transport code System (PHITS) to obtain the predicted annihilation photon distributions. The range of beams in the phantom was determined by comparing measured and simulated planar-integrated annihilation photon distributions (PIADs). Fisher information was used to quantify the expected accuracy of range determinations. Main results. The measured PIADs showed good agreement with the simulated PIADs for carbon, oxygen, and neon ions. However, discrepancies were observed for helium ions, likely due to uncertainties in the cross section data used in PHITS. The range was determined within an accuracy of 2 mm for four ion species for the measurement times longer than 3 min. Neon ions had the most Fisher information for measurement times shorter than 135 s, whereas beyond that, oxygen ions had the most information, offering the highest range determination accuracy. Significance. The range was determined within an accuracy of 2 mm for helium, carbon, oxygen, and neon ion beams by the OpenPET measurements of 180 s. Among the four ion species, neon ions showed the highest accuracy in range determination within 135 s, while oxygen ions performed best for measurement times beyond 135 s.